FDI in Multi-brand Retailing in India: Comparative study with China - Jain, Dr. Anuradha (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Retailing is the interface between the producer and the individual consumer buying for personal consumption. As such, retailing is the last link that connects the individual consumer with the manufacturing and distribution chain. Indian retail industry is one of the sunrise sectors with huge growth potential. However, in spite of the recent developments in retailing and its immense contribution to the economy, retailing continues to be the least evolved industries and the growth of organised retailing in India has been much slower as compared to rest of the world. This paper captures the existing retail scenario in India with regard to organized and un-organized retail and presents the limitations of the current set-up along with the experiences of domestic players. The paper discusses about opening up of the multibrand retail sector to foreign direct investment by the government. The rationale for retail reforms and challenges to be addressed by the retail sector are discussed. FDI in Retail is like an allopathic medicine It would deliver quick results & would not work as hit & trial like Homeopath. Government must go for Policy Mix to avoid its side effects. It will require various changes in internal policies also. The whole process must be made socially & economically useful.It will be better to follow the Chinese model of caution and hurrying slowly. China took over 12years to liberalise its FDI regime and in stages with reversals as well. The Chinese retail environment is 20years ahead of us. Looking at their market today can give us a rough idea of how FDI in multi brand retail in India might pan out in the medium term and long term period.